PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN DAN LOYALITAS ORANG TUA SISWA DI MI NU MIFTAHUL HUDA 02 PIJI DAWE KUDUS TAHUN PELAJARAN 2015/2016 (Pascasarjana IAIN Kudus, 2016)
This research aims to elucidate the influence of service quality against the satisfaction and loyalty of students’ parents in MI NU Miftahul Huda 02 Piji Dawe Kudus year 2015/2016. The respondents in this study are 87 of students’ parents. The analysis used is the path analysis with the help of SPSS 17. The research and discussion results showed that: (1) the service quality in MI NU Miftahul Huda 02 Piji Dawe Kudus Year 2015/2016 according to researcher it was assessed quite well with the average value is 3.39; (2) satisfaction and loyalty of students’ parents in MI NU Miftahul Huda 02 Piji Dawe Kudus year 2015/2016 according to researcher it was assessed quite well and good with average value of 3.23 and 3.57; (3) influence of the service quality against the satisfaction and loyalty of students’ parents in MI NU Miftahul Huda 02 Piji Dawe Kudus year 2015/2016 according to the researcher it influential directly. It can be seen from the coefficient value of the service quality variable towards the satisfaction of parents 49.7% and the coefficient value of the service quality variable against the loyalty of parents 7.8%. This shows that the service quality can increase the parents’ satisfaction and loyalty against the institution.